SISTEM INFORMASI ASSEMBLING GUNA MENUNJANG KELENGKAPAN REKAM MEDIS RAWAT INAP DI RUMAH SAKIT AL ISLAM BANDUNG - Aulia Zeta Andhani (INFOKES (Informasi Kesehatan), 2020)
This research aimed to know the implementation of assembling in supporting the completeness inpatient medical record at Rumah Sakit Al Islam Bandung. The research method used was qualitative research method with descriptive approach. The data collecting method were used observing the implementation of analyzing the completeness inpatient medical record, interviewing and doing literature review which was relevant to the main problem. From this research, it was found that problems of the implementation of assembling were : (1). The absence of an integrated report daily from the main system; (2). The Duration of the search process files medical record; (3). Often the discovery of medical records without cover; (4). Misscomunication. The suggestion was given to improve the implementation of assembling and to improve quality of service that obtained at the completeness inpatient medical record, were as follows : (1). Creating the completeness inpatient medical record of the information system, the information system used to be concerned in terms of ergonomics, creating information system that was equepped safety to maintain the confidentiality of medical records; (2). Extending the incompleteness medical record keeping, so controlled by officers who was monitor the completeness inpatient medical record; (3). Increasing cooperation between medical records officers with other health workers.